Seizure-related hospital admissions, readmissions and costs: Comparisons with asthma and diabetes in South Australia. (August 2017) - Bellon, Michelle L.; Barton, Christopher; McCaffrey, Nikki; Parker, Denise; Hutchinson, Claire
Highlights: The rate of seizure hospitalisations was higher than diabetes yet lower than asthma. Highest proportions of subsequent separations were by children with seizures. Subsequent adult separations were higher for seizures than bronchitis/asthma and diabetes. Hospital costs for seizures were higher than asthma, yet lower than diabetes. Education and support through seizure clinics may reduce avoidable hospitalisations. Abstract: Purpose: Seizures are listed as an Ambulatory Care Sensitive Condition (ACSC), where, in some cases, hospitalisation may be avoided with appropriate preventative and early management in primary care. We examined the frequencies, trends and financial costs of first and subsequent seizure-related hospital admissions in the adult and paediatric populations, with comparisons to bronchitis/asthma and diabetes admissions in South Australia between 2012 and 2014. Methods: De-identified hospital separation data from five major public hospitals in metropolitan South Australia were analysed to determine the number of children and adults admitted for the following Australian Refined Diagnosis Related Groups: seizure related conditions; bronchitis/asthma; and diabetes. Additional data included length of hospital stay and type of admission. Demographic data were analysed to identify whether social determinants influence admission, and a macro costing approach was then applied to calculate the financial costs to the Health Care System. Results: The rate of total seizure hospitalizations was 649 per 100, 000; lower than bronchitis/asthma (751/100, 000), yet higher than diabetes (500/100, 000). The highest proportions of subsequent separations were recorded by children with seizures regardless of complexity (47% +CSCC; 17% −CSCC) compared with asthma (11% +CSCC; 14% −CSCC) or diabetes (14% +CSCC; 13% −CSCC), and by adults with seizures with catastrophic or severe complications/comorbidity (25%), compared with diabetes (22%) or asthma (14%). The mean cost per separation in both children and adults was highest for diabetes (AU$4438/$7656), followed by seizures (AU$2408/$5691) and asthma (AU$2084/$3295). Conclusions: Following the lead of well-developed and resourced health promotion initiatives in asthma and diabetes, appropriate primary care, community education and seizure management services (including seizure clinics) should be targeted in an effort to reduce seizure related hospitalisations which may be avoidable, minimise costs to the health budget, and maximise health care quality.